2020
DOI: 10.9734/mrji/2020/v30i730241
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Helicobacter pylori Infections and Associated Risk Factors among Cases of Iron Deficiency Anaemia in Egypt

Abstract: Introduction: Iron deficiency anaemia (IDA) is a worldwide nutritional problem; it accounts for about half of the world’s anaemia burden. Globally, Helicobacter pylori (H. pylori) is becoming an increasingly troublesome economic and public health problem. The colonization of the organism in gastric mucosa may impair iron uptake and increase iron loss, potentially leading to iron deficiency anaemia. The mechanisms by which H. pylori is postulated to cause IDA are H. pylori -associated chronic gastritis resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Microcytic hypochromic anemia is the most common type (87.9%) in H. pylori-infected group in this study. This was consistent with El-Kady et al 63 who reported that H. pylori infection significantly affected the Hb level, MCV, MCH, and red blood cells distribution width in studied cases. Meanwhile, H. pylori infection significantly affected the serum iron, serum ferritin, and total iron-binding capacity (TIBC) in studied cases of IDA.…”
Section: Discussionsupporting
confidence: 93%
“…Microcytic hypochromic anemia is the most common type (87.9%) in H. pylori-infected group in this study. This was consistent with El-Kady et al 63 who reported that H. pylori infection significantly affected the Hb level, MCV, MCH, and red blood cells distribution width in studied cases. Meanwhile, H. pylori infection significantly affected the serum iron, serum ferritin, and total iron-binding capacity (TIBC) in studied cases of IDA.…”
Section: Discussionsupporting
confidence: 93%
“…There were eight cross-sectional studies, 15,17,18,[27][28][29][30][31] six RCTs, 13,[32][33][34][35][36] five case-control studies, 12,16,20,21,37 two surveys, 11,38 and one cohort study. 14 Only six studies reported participants' average age, hemoglobin, and serum ferritin levels 14,20,28,29,31,36 (►Table 2). All included studies were of high quality (►Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…According to the World Bank classification of economic level, six studies 16,27,[31][32][33]35 with a total sample size of 2,086 were conducted in countries with lower middle incomes. In addition, eight studies 11,14,15,17,28,30,36,38 with a total sample size of 3,990 were from high incomes countries and eight 12,13,18,20,21,29,34,37 with a total sample size of 1,813 were from countries with upper middle incomes. Studies included in the meta-analysis were grouped according to the methods used to diagnose H. pylori.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation